Aplikasi Sistem Pakar Diagnosis Risiko Penyakit Kanker Paru Dengan Metode Forward Chaining Berbasis Android - Hendri Tri Cahya Leksana; Mutaqin Akbar (Journal Of Information System And Artificial Intelligence, 2022)
Early diagnosis of lung cancer, which is the number one cause of death in developed countries, is urgently needed. In general, lung cancer is caused by many things including an unhealthy environment, an unhealthy lifestyle and a lack of knowledge about the characteristics or symptoms that are signs that a person has a high or low risk of cancer. The acquisition of knowledge from experts, in this study, is an anatomical pathologist who specializes in obtaining a knowledge base. There are 50 selected respondents who are used as data in this study. The detectable risk is a low risk of lung cancer and a high risk of lung cancer. The forward chaining method is a method for calculating the confidence value of the symptoms given by a patient. The results of testing from 50 selected respondents got very good results for application assessment and application testing results are in accordance with the analysis of the informants by 70%.